Implementation Of Business Development Strategies To Improve Competitiveness At Bank Syariah Indonesia Surabaya - Shania Pradyptha Kusuma; Mutiara Latifah; Annisa Dwi Wulandari; Renny Oktavia (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
Islamic banking in Indonesia shows a positive growth trend, but still faces significant challenges in increasing competitiveness amidst tight competition between islamic banks and conventional banks. This indicates a gap between the potential of the Islamic finance market and its actual realization. This study aims to analyze the challenges and formulate strategies to enhance the competitiveness of Islamic banking, focusing on a case study of Bank Syariah Indonesia (BSI) KCP MERR and KCP PGS Surabaya. A descriptive qualitative approach was employed, utilizing semi-structured interviews with informants who had internship experience at BSI, along with a literature review of academic journals and secondary data such as official reports from the Financial Services Authority (OJK). The findings reveal that the main challenges faced by BSI include low Islamic financial literacy, limited digital innovation, and insufficient outreach in marketing strategies. The strategies implemented involve enhancing digital services, conducting intensive public education, and developing Sharia-compliant financial products based on market needs. The implications of this research are expected to provide practical recommendations for strengthening the competitiveness of Islamic banks nationally while promoting inclusive financial growth grounded in Islamic values.